Has the COVID-19 pandemic changed household food management and food waste behavior? A natural experiment using propensity score matching. (15th February 2023) - Ananda, Jayanath; Karunasena, Gamithri Gayana; Pearson, David
Abstract: Household food management behavior changed considerably during the COVID-19 pandemic. A growing body of work has quantified the impact of lockdowns on household food waste. Yet, previous studies used a retrospective study design which undermines the accuracy of the causal effect on household food waste. This paper investigates the causal impact of the COVID-19 pandemic on household food management and food waste using a natural experiment approach. Using two large national-scale longitudinal data sets (n = 8157), this study quantifies the impact of COVID-19 on food waste and food behavior of Australian households. Propensity score matching (PSM) was carried out to address potential endogeneity issues and to select control and treatment groups for analysis. Findings reveal that Australian households reduced food waste by 9% on average in 2020 (during COVID-19) compared to the pre-pandemic (2019) level. The use of a grocery list, discount purchases, and 'just-in-case' purchases, and food refrigeration have recorded a marked increase during the pandemic compared to pre-pandemic times. The changes to food management and food discard behavior during the pandemic offer important insights for behavior change campaigns to reduce household food waste. Interventions to sustain good food planning and storage practices and involving food retailers are promising entry points in addressing household food waste. The study also highlights the considerable challenge in achieving SDG 12.3 target by 2030. Graphical abstract: Image 1 Highlights: Natural experiment on food waste behaviour using propensity score matching. COVID-19 pandemic has changed the food behaviour of households. Household food waste reduced significantly during pandemic lockdowns. Food planning, purchasing and storage behaviours showed improvements. Meeting the Sustainable Development Goal 12.3 may be challenging than anticipated.